2007
DOI: 10.1016/j.crme.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Joseph Boussinesq (1842–1929): a pioneer of mechanical modelling at the end of the 19th Century

Abstract: Researchers in Mechanics who have never heard the name of Joseph Boussinesq are few. Boussinesq first taught at the Faculty of Sciences in Lille for about fifteen years, then, after being elected to the Academy of Sciences in Paris, taught there for over forty years. From his work, both in Lille and in the Academy of Sciences, he left a great many publications, touching on a variety of subjects, as proof of his many talents. Oddly enough, however, Boussinesq is almost always known to the world of scientific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 36 publications
0
4
0
1
Order By: Relevance
“…The Oberbeck-Boussinesq approximation, so named after the pioneering works by Oberbeck [1] and Boussinesq [2], is the basis of most of the contemporary studies on natural or mixed convection flows. Very interesting historical surveys on the origins of this approximation are available in the recent papers by Zeytounian [3] and Bois [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Oberbeck-Boussinesq approximation, so named after the pioneering works by Oberbeck [1] and Boussinesq [2], is the basis of most of the contemporary studies on natural or mixed convection flows. Very interesting historical surveys on the origins of this approximation are available in the recent papers by Zeytounian [3] and Bois [4].…”
Section: Introductionmentioning
confidence: 99%
“…The applicability of Boussinesq approximation [5,6] is limited to an initial fractional density 0 / a ρρ ∆ of 0.05 [7] where 0 ρ is the density at the source and ρ a is the ambient density, but to generalize this approximation Swain et al [8] suggested a condition of 0 /1 a ρρ ∆ 0 for jets of light fluid injected into an ambient environment of high density. In these cases where Boussinesq approximation is invalid, a density equation must be taken into consideration.…”
Section: General Hypothesismentioning
confidence: 99%
“…The averaged Navier-Stokes equations are also called Reynolds equations. The numerical solution of these equations requires the use of a turbulence model as suggested by Boussinesq for the first time [2].…”
Section: Introductionmentioning
confidence: 99%